Airway epithelial barrier, mucins and inflammasome in distinct eosinophilic, neutrophilic and mixed inflammatory phenotypes of asthma - Tze, Tan Hern (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2018)
Introduction Asthma is a complex, chronic respiratory disease with marked clinical and pathophysiological heterogeneity. Specific pathways are thought to be involved in the pathomechanisms of different inflammatory phenotypes of asthma, yet direct in vivo comparison has not been performed. In the present study, we aimed to investigate the expression of tight junction molecules, mucins and inflammasome activation in different phenotypes of airway inflammation. Method We developed models of three different phenotypes of airway inflammation in mice, namely · eosinophilic, mixed, and neutrophilic asthma via different methods of house dust mite , sensit isation and challenge. Transcriptome analysis was performed using whole lung tissues, fol lowed by quantitative RT-PCR, western blot analysis and confocal microscopy. Results By unbiased whole genome transcriptomic approach, we found that airway tight junction (TJ) molecules, mucins and inflammasome-related genes are differentially expressed in distinct phenotypes of allergic airway inflammation. Detailed analysis of several molecules from these families revealed that (i) Zo-1 and Cldn18 were downregulated in all phenotypes, while Cldn4 upregulation was characteristic for neutrophilic airway inflammation; (ii) mucins Clcal (GobS) and MucSac were upregulated in eosinophilic and even more in neutrophilic asthma, and (iii) upregulation of inflammasome-related molecules such as Nlrp3, Nlrc4, casp-1 and IL-113 was characteristic for neutrophilic asthma. Finally, we showed that inflammasome/Th· 17 /neutrophilic axis cytokines, namely IL-113 and IL-17, might impair epithelial barrier function and increase mucins expressions in primary hBECs from normal and asthmati< donors. Conclusion Our findings suggest that differential expression of TJs, mucins and inflammasome-relate<: molecules in distinct asthma phenotypes might be mechanistically linked and could further reflect the differences observed in the clinic.